A family affair: the depiction of disability in contemporary mainstream Italian cinema. Issue 2 (May 2014) - Hill, Sarah Patricia
Abstract : Despite a grim history of marginalisation and oppression of people with disabilities, Italy has been praised for its early de-institutionalisation and attempts to adopt a more inclusive educational approach. Do recent Italian films provide evidence that these approaches have made a difference to how disability is made visible on film, or is it still depicted largely as an individual or family affair rather than a societal or political issue? Over the last decades, numerous scholars in disability studies have argued that cinema is an important location for understanding the formation of ideas about disability and have analysed the representation of people with disabilities in film, particularly in mainstream cinema. Moving from a focus on stereotypes and the description of 'positive' and 'negative' portrayals of disability, more recent scholarship examines filmic images of people with impairments in the light of a conception of disability termed by Snyder and Mitchell a 'constructed social space'. Yet this extensive body of work has had limited impact in Italy in disability studies and film studies. This article applies it to some contemporary Italian films, considering the ways in which they represent disability and focusing in particular on Andrea Molaioli's La ragazza del lago (2007).